Influence Entrepreneurial Orientation on Sustainable Organizational Performance mediated Technology Resources - Husein, M Adam; Santoso, Andri Budi; Asri, Tika Kartika; Poernomoputri, Tyara Pratiwi (CV. Rayyan Dwi Bharata, 2024)
Purpose: This research aims to see the influence of Entrepreneurial Orientation variables on Sustainable Organizational Performance by using Technology Resources as a mediator. Discussion of sustainable organizational performance in cooperatives is very important because cooperatives are one of the pillars of the economy in Indonesia. This research uses quantitative causality methods. The population of this research was 30 employees at Kopsyah BMI in the Bogor area, all of whom were used as respondents. The data analysis method uses Structural Equation Model-Partial Least Square (SEM-PLS). The research results prove that Entrepreneurial Orientation has a positive influence on Sustainable Organizational Performance. Technology Resources had a positive influence on Sustainable Organizational Performance, so Technology Resources be a mediating role in the influence of Entrepreneurial Orientation on Sustainable Organizational Performance. The Study extends previous research, adding Technological Resources as a mediation between the influence of Entrepreneurial Orientation on Sustainable Organizational Performance.